Effects of Endurance and Endurance Strength Training on Body Composition and Physical Capacity in Women with Abdominal Obesity - Skrypnik, Damian (Obes Facts, 2015)
AIMS: To compare the effects of endurance training with endurance strength training on the anthropometric, body composition, physical capacity, and circulatory parameters in obese women. METHODS: 44 women with abdominal obesity were randomized into groups A and B, and asked to perform endurance (A) and endurance strength training (B) for 3 months, 3 times/week, for 60 min. Dual-energy X-ray absorptiometry and Graded Exercise Test were performed before and after training. RESULTS: Significant decreases in body mass, BMI, total body fat, total body fat mass, and waist and hip circumference were observed after both types of intervention. Marked increases in total body lean and total body fat-free mass were documented in group B. In both groups, significant increases in peak oxygen uptake, time to exhaustion, maximal work rate, and work rate at ventilatory threshold were accompanied by noticeably decreased resting heart rate, resting systolic blood pressure, and resting and exercise diastolic blood pressure. No significant differences were noticed between groups for the investigated parameters. CONCLUSION: Our findings demonstrate evidence for a favorable and comparable effect of 3-month endurance and endurance strength training on anthropometric parameters, body composition, physical capacity, and circulatory system function in women with abdominal obesity.